Solve for x, y, z
x=\frac{a}{3}+22
y=-\frac{a}{3}+18
z=a
Share
Copied to clipboard
z=x-2y+14 x+y-40=0 a=z
Reorder the equations.
a=x-2y+14
Substitute x-2y+14 for z in the equation a=z.
y=-x+40 x=2y+a-14
Solve the second equation for y and the third equation for x.
x=2\left(-x+40\right)+a-14
Substitute -x+40 for y in the equation x=2y+a-14.
x=22+\frac{1}{3}a
Solve x=2\left(-x+40\right)+a-14 for x.
y=-\left(22+\frac{1}{3}a\right)+40
Substitute 22+\frac{1}{3}a for x in the equation y=-x+40.
y=18-\frac{1}{3}a
Calculate y from y=-\left(22+\frac{1}{3}a\right)+40.
z=22+\frac{1}{3}a-2\left(18-\frac{1}{3}a\right)+14
Substitute 18-\frac{1}{3}a for y and 22+\frac{1}{3}a for x in the equation z=x-2y+14.
z=a
Calculate z from z=22+\frac{1}{3}a-2\left(18-\frac{1}{3}a\right)+14.
x=22+\frac{1}{3}a y=18-\frac{1}{3}a z=a
The system is now solved.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}